Media and Methods in Promoting Dental and Oral Health among Pregnant Women - Ferdiana Maharani; Syamsulhuda Budi Musthofa; Farid Agushybana (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: The health of pregnant women is influenced by what they consume. Consuming good food but having infections or abnormalities in the mouth and teeth will cause the incoming food to be contaminated and will have an impact on the baby's growth and development. Based on this, dental and oral health in pregnant women plays a very important role for pregnant women and children. This study aims to find out how analysts promote dental and oral health in pregnant women. The method used is a systematic literature review using the PRISMA diagram by identifying P (Population, patients), Intervention (Intervention or treatment), Prognostic Factors, or Exposure, Comparison (comparison with control if any), Outcome (outcome) according to the research to be conducted, and Study (type of research). From the results of the reduction of selected journals, there are 19 scientific articles that will be analyzed. Review: In this research, there are various health promotions that can be carried out to provide education to the public, including social media, consultations, hospitals, training, providing video demonstrations and explanations via flip charts Conclusions: The conclusion of this research is that there are various health promotions that can be carried out to provide education to the public, including social media, consultations, hospitals, training, providing video demonstrations and explanations via flip charts. The suggestion from this research is the need for intensive health promotion and health education for pregnant women. Promotion and education can be carried out by residents in collaboration with community health centers or in collaboration with hospitals or can also be done through social media.